Diosmin and Trolox Have Anti-Arthritic, Anti-Inflammatory and Antioxidant Potencies in Complete Freund's Adjuvant-Induced Arthritic Male Wistar Rats: Roles of NF-κB, iNOS, Nrf2 and MMPs - Huda H. Shaaban; Walaa G. Hozayen; Amal K. Khaliefa; Ayman E. El-Kenawy; Tarek M. Ali; Osama M. Ahmed (MDPI AG, 2022)
Rheumatoid arthritis (RA) is a chronic, progressive, autoimmune disease caused by a malfunction of the immune system. The aim of this study was to examine the anti-arthritic effects and suggest the mechanisms of actions of diosmin and trolox in male Wistar rats. Complete Freund's adjuvant (CFA) was used to establish RA in the animals by subcutaneous injection of 100 µL CFA/rat into plantar region of right hind leg in two consecutive days. Diosmin and/or trolox were administered orally at a dosage of 20 mg/kg/day to CFA-induced arthritic rats for 2 weeks. The normal and arthritic control groups were orally given the same equivalent volume of a vehicle (1% carboxymethyl cellulose) in which treatment agents were dissolved. At the end of the experiment, blood samples were collected from the jugular vein for the detection of the total leukocyte count (TLC) and differential leukocyte count (DLC) in blood and the detection of rheumatoid factor (RF), anti-citrullinated protein antibodies (ACPA), tumor necrosis factor-α (TNF-α), interleukin-13 (IL-13), and interleukin-17 (IL-17) levels by enzyme-linked immunosorbent assay (ELISA), as well as markers of oxidative stress and the antioxidant defense system in serum. The right hind ankle regions of three rats from each group were dissected out and fixed in 10% neutral-buffered formalin for histological examination and the other three were kept at −30 °C for Western blot analysis of nuclear factor-kappa B (NF-κB) protein 50 (NF-κB p50), NF-κB p65, inducible nitric oxide synthase (iNOS), nuclear factor erythroid-2-related factor 2 (Nrf2), and matrix metalloproteinase (MMP)-1 (MMP-1), MMP-3, and MMP-9. The CFA injection was deleterious to the ankle joint's histological architecture, manifesting as infiltration of inflammatory cells into the articular cartilage, hyperplasia of the synovium, and erosion of the cartilage. All these effects were ameliorated by diosmin and/or trolox, with the combined dose being the most effective. The two compounds significantly lowered the elevated serum levels of RF, ACPA, TNF-α, and IL-17, as well as other pro-inflammatory mediators, such as NF-κB p50, NF-κB p65, iNOS, MMP-1, MMP-3 and MMP-9. They also increased the levels of the anti-inflammatory cytokine, IL-13, and the cytoprotective transcription factor Nrf2. The compounds stimulated higher activities of antioxidants, such as glutathione, glutathione-S-transferase, catalase, and superoxide dismutase, and reduced lipid peroxidation in the serum of arthritic rats. In conclusion, diosmin, trolox, and their combination, which was the most potent, exerted anti-arthritic, anti-inflammatory and antioxidant effects by suppressing NF-κB signaling, inhibiting matrix metalloproteinases, and activating Nrf2.